ANALISIS EFEKTIVITAS PROMOSI KULINER DI WAROENG KLANGENAN YOGYAKARTA - , AINUN KURNIA SARI, Prof. Dr. Marsono, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Promotion strategy are advertising, personal selling, promotion selling, public relation and direct selling that company used for communicated consumer value with persuasive and build consumer relationship. Waroeng Klangenan is a new culinary industry in Yogyakarta. Waroeng Klangenan since about 6 mounts ago, but very much tourist come in. They have come a consumer with promotion mix strategy. The purpose from this research for to know and analysed promotion strategy that used in Waroeng Klangenan. In this research used research method qualitative descriptive, data collecting used an observation, interview and book study. Result of research is Waroeng Klangenan used a promotional mix for explain the product to the tourist. Market target is younger until old people so all the people can enjoy the product of Waroen g Klangenan. Promotional mix strategy are advertising and for advertising Waroeng Klangenan use a radio, brochure, culinary magazine, and an announcement about soft opening that all people can come in and eat for free. Personal selling are make a cooperation with local tour guide and hotels, promotion selling are used an coupon for people that have a ticket of minak jingo menggugat show and they have a discount, public relations are used their consumer for their publicity to each other, they come with another friends and that is how Waroeng Klangenan make an relationship with their consumer. If they want to make a cooperate with the owner they have 10% for commission. And the last is direct selling are used a social media, they used facebook and twitter also foursquare as their media to connect with their consumer and make a business relationship. Keywords : Promotion mix, Advertising, Personal Selling, Promotion Selling, Public Relations, Direct Selling.